Post-koiné, or Anita Jarzyna’s Project of Non-anthropocentric Criticism - Czerska, Tatiana (Porównania, 2021)
The article below is an overview and discussion of Anita Jarzyna Post-koiné’s monograph. Studies on non-anthropocentric (poetic) languages, which is one of the key treatises examining human-animal relationships on the material of Polish poetry of the 20th and 21st centuries. Jarzyna’s book is not only an example of skilful application of methodologies from the border of posthumanism and animal studies. It is an original and innovative proposition of a non-anthropocentric reading of literature. It is also an important voice in the debate on building an ecological order and the place and role of animals in human life.